2003
DOI: 10.4315/0362-028x-66.12.2245
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella during Drying and Storage of Apple Slices Treated with Acidic or Sodium Metabisulfite Solutions

Abstract: This study was undertaken to determine whether pretreating inoculated Gala apple slices with metabisulfite or acidic solutions enhanced the inactivation of Salmonella during dehydration and storage. Apple slices inoculated with a five-strain mixture of Salmonella (7.6 log CFU/g) were pretreated, dried for 6 h at 60 degrees C, and stored aerobically at 25 degrees C for 28 days. Predrying treatments included (i) no treatment, (ii) 10 min of immersion in sterile water, (iii) 10 min of immersion in a 4.18% sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
2
31
0
2
Order By: Relevance
“…Interestingly, acid-adapted cells did not mount tolerance to desiccation and, in fact, were more susceptible to this stress. Likewise, exposure of Salmonella-contaminated tomato or apple slices to acids (ascorbic and citric acids) also reduced Salmonella survival following dehydration (15,52). Thus, prechallenge to a single stress does not necessarily result in the development of tolerance to another stress.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, acid-adapted cells did not mount tolerance to desiccation and, in fact, were more susceptible to this stress. Likewise, exposure of Salmonella-contaminated tomato or apple slices to acids (ascorbic and citric acids) also reduced Salmonella survival following dehydration (15,52). Thus, prechallenge to a single stress does not necessarily result in the development of tolerance to another stress.…”
Section: Discussionmentioning
confidence: 94%
“…Although sodium metabisulphite is also a known antimicrobial (DiPersio et al 2003) it is not equally active against all microorganisms (Barnett 1985), in all foods (DiPersio et al 2003) or under all storage conditions . Although this compound is used to treat blackspot in cholera-endemic countries, no information on its effect on the survival of V. cholerae or prawn safety is readily available.…”
Section: Introductionmentioning
confidence: 99%
“…In the spring of 2001, we conducted a survey of home‐fruit drying recommendations made by the CES. Information was gathered from 27 states (DiPersio et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies evaluating the various recommended drying methods have shown that treating with an ascorbic or citric acid solution also enhances inactivation of pathogenic bacteria during dehydration and storage (Burnham et al. 2001; DiPersio et al. 2003; Derrickson‐Tharrington et al.…”
Section: Introductionmentioning
confidence: 99%